Autism symptoms, functional impairments, and gaze fixation measured using an eye-tracker in 6-year-old children - Mori, Toko; Tsuchiya, Kenji J.; Harada, Taeko; Nakayasu, Chikako; Okumura, Akemi; Nishimura, Tomoko; Katayama, Taiichi; Endo, Masayuki (Frontiers in Psychiatry, 2023)
Introduction: Autism spectrum disorder (ASD) is a neurodevelopmental disorder clinically characterized by abnormalities in eye contact during social exchanges. We aimed to clarify whether the amount of gaze fixation, measured at the age of 6 years using Gazefinder, which is an established eye-tracking devices, is associated with ASD symptoms and functioning. Methods: The current study included 742 participants from the Hamamatsu Birth Cohort Study. Autistic symptoms were evaluated according to the Autism Diagnostic Observation Schedule Second Edition (ADOS-2) and functioning of the participating children in real-life was assessed using the Japanese version of the Vineland Adaptive Behavior Scales, Second Edition (VABS-II). The Gazefinder system was used for gaze fixation rates; two areas of interest (eyes and mouth) were defined in a talking movie clip and eye gaze positions were calculated through corneal reflection techniques. Results: The participants had an average age of 6.06 +/- 0.14 years, (males: 384;52%). According to ADOS, 617 children (83%) were assessed as having as none/mild ASD and 51 (7%) as severe. The average VABS-II scores were approximately 100 (SD=12). A higher gaze fixation rate on eyes was associated with a significantly lower likelihood of the child being assigned to the severe ADOS group, after controlling for covariates (OR, 0.02; 95% CI, 0.002–0.38). The gaze fixation rate on mouth was not associated with ASD symptoms. A higher gaze fixation rate on mouth was associated with a significantly lower likelihood of the child being assigned to the low score group in VABS- II socialization, after controlling for covariates (OR, 0.18; 95% CI, 0.04–0.85). Gaze fixation rate on eyes was not associated with functioning. Conclusions: We found that children with low gaze fixation rates on eyes were likely to have more ASD symptoms, and children with low gaze fixation rates on mouth were likely to demonstrate poorer functioning in socialization. Hence, preschool children could be independently assessed in the general population for clinically-relevant endophenotypes predictive of ASD symptoms and functional impairments.